Complexidade do sistema nervoso autônomo em indivíduos com DPOC - Vanzella, Laís Manata [UNESP]; Bernardo, Aline Fernanda Barbosa [UNESP]; De Carvalho, Tatiana Dias; Vanderlei, Franciele Marques [UNESP]; Da Silva, Anne Kastelianne França [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (FapUNIFESP (SciELO), 2018)
Objective: To evaluate autonomic modulation in individuals with COPD, compared with healthy controls, via recurrence plots (RPs) and linear heart rate variability (HRV) indices. Methods: We analyzed data on 74 volunteers, who were divided into two groups: COPD (n = 43) and control (n = 31). For calculation of HRV indices, heart rate was measured beat-by-beat during 30 min of supine rest using a heart-rate meter. We analyzed linear indices in the time and frequency domains, as well as indices derived from the RPs. Results: In comparison with the control group, the COPD group showed significant increases in the indices derived from the RPs, as well as significant reductions in the linear indices in the time and frequency domains. No significant differences were observed in the linear indices in the frequency domains expressed in normalized units or in the low frequency/high frequency ratio. Conclusions: Individuals with COPD show a reduction in both sympathetic and parasympathetic activity, associated with decreased complexity of autonomic nervous system function, as identified by RPs, which provide important complementary information in the detection of autonomic changes in this population.
Complexity of autonomic nervous system function in individuals with COPD
Keywords: Autonomic nervous system; Chronic obstructive; Heart rate; Nonlinear dynamics; Pulmonary disease; Recurrence; Sympathetic nervous system